2015
DOI: 10.9767/bcrec.10.2.7734.185-191
|View full text |Cite
|
Sign up to set email alerts
|

Facile Oxidative Desulfurisation of Benzothiophene Using Polyoxometalate H4[α-SiW12O40]/Zr Catalyst

Abstract: A highly active catalyst H4[α-SiW12O40]/Zr based polyoxometalete Keggin type was prepared by wet impregnation method and was characterized by FTIR spectroscopy, X-ray diffractometer, surface textural property by SEM, and analysis of porosity by BET method. H4[α-SiW12O40]/Zr was successfully synthesized and showed uniform properties with block solid structure which was applied as heterogeneous stable catalyst for oxidative desulfurization of benzothiophene under simple and mild condition using H2O2 as oxidant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The catalytic data shows that high temperature is directly proportional to the high %conversion of DBT. Desulfurization of DBT using H 2 O 2 is better at high temperatures by converting DBT to DBT-sulfone (Fraile et al, 2016;Lesbani et al, 2015). Desulfurization of DBT at 50°C is better than at 30°C and 40°C.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic data shows that high temperature is directly proportional to the high %conversion of DBT. Desulfurization of DBT using H 2 O 2 is better at high temperatures by converting DBT to DBT-sulfone (Fraile et al, 2016;Lesbani et al, 2015). Desulfurization of DBT at 50°C is better than at 30°C and 40°C.…”
Section: Resultsmentioning
confidence: 99%
“…The data in Figure 8 showed that H4[α-SiW12O40]/Zr as catalyst for oxidation of cyclohexane was used optimum at 0.038 g. In the catalytic process, the use of catalyst was recommended less than 1/10 mmol of reactan and the amount of catalyst 0.038 g in this research was suitable for the oxidation. The weight of H4[α-SiW12O40]/Zr was optimized because hydrogen peroxide is mild oxidant and need activation to produce radical oxygen for substitution into reactant (Lesbani et al, 2015b). The oxidation of cyclohexane in this research was conducted in heterogeneous system and H4[α-SiW12O40]/Zr was not dissolved into reaction medium.…”
Section: Resultsmentioning
confidence: 99%
“…Lesbani et.al (2015) was used zirconium oxide for supporting Keggin type polyoxometalate H4[-SiW12O40] as catalyst for desulfurization [5]. Supporting polyoxometalate with metal oxide also exhibit catalytic activity for desulfurization of benzothiophene [6].…”
Section: Abstrak (Indonesian)mentioning
confidence: 99%